Tcirg1 deficiency delays osteoarthritis progression by impairing lysosome acidification and peripheral accumulation in osteoclasts - Sun, Rui; Yang, Yang; Ma, Qi; Wu, Gang; Lan, Zhibin; Xue, Di; Chen, Zhirong; Su, Yajing; Tuo, Zhaopu; Yan, Jiangbo; Ma, Long; Zhao, Xin; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionOsteoarthritis (OA) is a chronic degenerative joint disease characterized by articular cartilage loss and aberrant subchondral bone remodeling. “T-cell immune regulator 1” (Tcirg1), which encodes the a3 subunit of the V-ATPase, has been demonstrated to inhibit the formation of large osteoclasts by reducing intracellular calcium oscillations. Mutations in the Tcirg1 gene sequence have been associated with osteopetrosis by impairing lysosomal transport in osteoclasts. This study aims to assess the impact of Tcirg1 on OA progression and to explore its therapeutic potential for the disease treatment.MethodsProteomic comparison of weight-bearing region (WBR) versus non-weight-bearing region (NWBR) of the subchondral bone was performed in 20 OA patients undergoing total knee arthroplasty. OA was then surgically induced in wild-type and Tcirg1-knockout mice by destabilization of the medial meniscus; disease severity and subchondral bone architecture were evaluated by histology and micro-CT. In vitro, primary bone marrow macrophages were differentiated into osteoclasts to assess the role of Tcirg1 in osteoclastogenesis, focusing on cell fusion, bone resorption, and lysosome acidification and distribution.Results and discussionProteomic analysis revealed that TCIRG1 was significantly upregulated in the WBR compared to NWBR of subchondral bone in OA patients, with functional enrichment analysis indicating TCIRG1 correlation with lysosome-related biological processes. In the murine OA model, Tcirg1 expression increased in parallel with osteoclast activity, peaking at 4 weeks post-surgery, which coincided with severe subchondral bone loss. Tcirg1 deficiency in knockout mice delayed OA progression, as evidenced by reduced cartilage damage, improved subchondral bone mass, and decreased osteoclast activity. In vitro, Tcirg1 expression increased during osteoclast differentiation, and its knockdown inhibited osteoclast fusion and bone resorption by impairing lysosome acidification and peripheral accumulation.ConclusionTcirg1 regulates lysosome acidification and peripheral accumulation, thereby influencing osteoclast activity in the subchondral bone. Given that Tcirg1 knockdown was found to slow down the progression of OA, targeting Tcirg1 may serve as a potential therapeutic strategy for treating OA.